Adaptive Hybrid Optimisation For Digital Colourisation: Implementations And Applications - Ann, Lai Min (2010)
Colourisation is a process of adding colour information onto a monochrome image or video frame. The advancement in digital computing technology reduces the tedious manual colouring process. The common colourisation process normally involves image segmentation and colouring of each segmented region. Both tasks required user interaction either in the image segmentation process or in the colouring process. Recent development of colourisation technique eliminates the trouble of precise image segmentation process by limiting the colour flow along the object boundary through the luminance intensity anlaysis.